Efeito de protocolos de treinamento com diferentes durações das ações musculares na resposta eletromiográfica - Cinara Gonçalves Costa (2012)
The manipulation of the duration of the repetition in strength training may influence the electromyographic responses. It still remains to be investigated whether different settings of the duration of muscle actions in training protocols with the same duration of the repetition could also change these responses. The aim of this study was to compare the electromyographic signal amplitude among sets and among training protocols with different durations of muscle actions and same duration of the repetition. Nineteen male volunteers with at least six months in strength training took part in this study. In the experimental sessions 1 and 2 subjects performed tests of one repetition maximum (1RM) in Smith machine bench press. In the experimental sessions 3, 4 and 5, three training protocols were performed in the Smith machine bench press, characterized by three sets of six repetitions at 60% of one repetition maximum (1RM) and three minutes of rest interval among sets. The training protocols presented different durations of muscle actions (Protocol 2-4: 2s for concentric and 4s for eccentric; Protocol 3-3: 3s for concentric and 3s for eccentric; Protocol 4-2: 4s for concentric and 2s for eccentric). The protocols were randomly and balanced assigned over the experimental sessions. The electromyographic signal amplitude of each repetition to the muscles pectoralis major and triceps brachii was quantified by the integral of the normalized electromyographic signal obtained by the average of repetitions performed in each set of the training protocols. For the pectoralis major, the protocol 4-2 showed higher normalized iEMG than the protocols 3-3 and 2-4. For the triceps brachii, protocols 4-2 and 3-3 showed higher normalized iEMG than the protocol 2-4. In both protocols, there was an increase in iEMG during the sets. The results of this study showed that a training protocol with greater time under tension in concentric muscle action induces an increased normalized iEMG of the pectoralis major and triceps when the protocols with the biggest differences in the duration of this action were compared. When protocols with smallest differences in the duration of the concentric muscle action were compared, the response of the normalized iEMG was different for the pectoralis major and triceps brachii.